Recurrent reciprocal 16p11.2 rearrangements associated with global developmental delay, behavioural problems, dysmorphism, epilepsy, and abnormal head size. Issue 5 (12th November 2009) - Shinawi, Marwan; Liu, Pengfei; Kang, Sung-Hae L; Shen, Joseph; Belmont, John W; Scott, Daryl A; Probst, Frank J; Craigen, William J; Graham, Brett H; Pursley, Amber; Clark, Gary; Lee, Jennifer; et al.
Abstract : Background: Deletion and the reciprocal duplication in 16p11.2 were recently associated with autism and developmental delay. Method: We indentified 27 deletions and 18 duplications of 16p11.2 were identified in 0.6% of all samples submitted for clinical array-CGH (comparative genomic hybridisation) analysis. Detailed molecular and phenotypic characterisations were performed on 17 deletion subjects and ten subjects with the duplication. Results: The most common clinical manifestations in 17 deletion and 10 duplication subjects were speech/language delay and cognitive impairment. Other phenotypes in the deletion patients included motor delay (50%), seizures (∼40%), behavioural problems (∼40%), congenital anomalies (∼30%), and autism (∼20%). The phenotypes among duplication patients included motor delay (6/10), behavioural problems (especially attention deficit hyperactivity disorder (ADHD)) (6/10), congenital anomalies (5/10), and seizures (3/10). Patients with the 16p11.2 deletion had statistically significant macrocephaly (p<0.0017) and 6 of the 10 patients with the duplication had microcephaly. One subject with the deletion was asymptomatic and another with the duplication had a normal cognitive and behavioural phenotype. Genomic analyses revealed additional complexity to the 16p11.2 region with mechanistic implications. The chromosomal rearrangement was de novo in all but 2 of the 10 deletion cases in which parental studies were available. Additionally, 2 de novo cases were apparently mosaic for the deletion in the analysed blood sample. Three de novo and 2 inherited cases were observed in the 5 of 10 duplication patients where data were available. Conclusions: Recurrent reciprocal 16p11.2 deletion and duplication are characterised by a spectrum of primarily neurocognitive phenotypes that are subject to incomplete penetrance and variable expressivity. The autism and macrocephaly observed with deletion and ADHD and microcephaly seen in duplication patients support a diametric model of autism spectrum and psychotic spectrum behavioural phenotypes in genomic sister disorders.